Outcomes of Elective Induction of Labor at 39 Weeks from a Statewide Collaborative Quality Initiative - Langen, Elizabeth S.; Schiller, Amy J.; Moore, Kathryn; Jiang, Charley; Bourdeau, Althea; Morgan, Daniel M.; Low, Lisa Kane (American Journal of Perinatology, 2023)
Objective This article evaluates the impact of adopting a practice of elective induction of labor (eIOL) at 39 weeks among nulliparous, term, singleton, vertex (NTSV) pregnancies in a statewide collaborative.Study Design We used data from a statewide maternity hospital collaborative quality initiative to analyze pregnancies that reached 39 weeks without a medical indication for delivery. We compared patients who underwent an eIOL versus those who experienced expectant management. The eIOL cohort was subsequently compared with a propensity score-matched cohort who were expectantly managed. The primary outcome was cesarean birth rate. Secondary outcomes included time to delivery and maternal and neonatal morbidities. Chi-square test, t-test, logistic regression, and propensity score matching methods were used for analysis.Results In 2020, 27,313 NTSV pregnancies were entered into the collaborative's data registry. A total of 1,558 women underwent eIOL and 12,577 were expectantly managed. Women in the eIOL cohort were more likely to be ≥35 years old (12.1 vs. 5.3%, p < 0.001), identify as white non-Hispanic (73.9 vs. 66.8%, p < 0.001), and be privately insured (63.0 vs. 61.3%, p = 0.04). When compared with all expectantly managed women, eIOL was associated with a higher cesarean birth rate (30.1 vs. 23.6%, p < 0.001). When compared with a propensity score-matched cohort, eIOL was not associated with a difference in cesarean birth rate (30.1 vs. 30.7%, p = 0.697). Time from admission to delivery was longer for the eIOL cohort compared with the unmatched (24.7 ± 12.3 vs. 16.3 ± 11.3 hours, p < 0.001) and matched (24.7 ± 12.3 vs. 20.1 ± 12.0 hours, p < 0.001) cohorts. Expectantly managed women were less likely to have a postpartum hemorrhage (8.3 vs. 10.1%, p = 0.02) or operative delivery (9.3 vs. 11.4%, p = 0.029), whereas women who underwent an eIOL were less likely to have a hypertensive disorder of pregnancy (5.5 vs. 9.2%, p < 0.001).Conclusion eIOL at 39 weeks may not be associated with a reduced NTSV cesarean delivery rate.Key Points
Keywords: induction of labor; cesarean birth; birth equity; vaginal birth